Experiences of Biological Parents and Their Older Children in Out-of-Home Care for the First Time. - Gourdine, Ruby M.; Smith, Jacqueline M.; Brown, Annie W. (Journal of Human Behavior in the Social Environment)
This article will examine the parenting characteristics and challenges that faced a cohort of families participating in an exploratory qualitative research study. This study sought to describe the experiences and characteristics of parents whose children were placed in the child welfare system in early-to-late adolescence (ages 12–18), thus gaining an understanding of the parenting challenges faced as they were able to maintain their children in their homes for a significant portion of their lives. The families of older youths entering care for the first time described how alcohol and drug abuse impacted their relationships with children, significant others, jobs, and their mental health status. A significant issue that emerged in several of the cases were older children who initiated a report to child welfare themselves.